Participation in Sustainable Forest Management : Linking Forests and People in Kenya - World Bank (Washington, DC, 2014)
This forest policy note was prepared to provide input to the ongoing forest sector reform in Kenya on participation in sustainable forest management. It offers recommendations on possible priority forest policy actions within the forthcoming Natural Resource Management (NRM) Project. The latter focuses enhancing the capacity of Kenyans to manage the natural resource base and resources available to poor and vulnerable communities. By outlining priority actions, such as improving the forest information base and establishing accountability mechanisms, while at the same time seizing the opportunities for engagement of local communities and private investors, the policy note outlines a set of actions critical for increased participation in sustainable forest management. In this respect the policy note supports the World Bank's Country Assistance Strategy (CAS) and the more recent CAS progress report. The latter emphasizes the Bank's strategy on growth and poverty reduction, but gives enhanced attention to equity and governance. The forest policy note complements previous the World Bank-supported analytical work in the forest sector since 2004, including a strategic environmental assessment of the 2005 Forests Act. Taking into account the importance of forests and woodlands in rural areas and the opportunities offered in the 2005 Forest Act for increased stakeholder participation the policy note as well as the forthcoming NRM Project are closely aligned the Bank Group's strategic emphasis on growth and poverty reduction with enhanced attention to equity and governance.